Music for Ages 0 to 3 Years (Journal of Parents and Teachers, 2025)
The article is divided into two sections. On one side, we find the song "Duérmete Niño" along with its objectives, activities, content, and observations. On the second page, the song "Se Abren y Se Cierran" is presented with the same items mentioned above.
Keywords: music and education; children